Landscape and urban planning approach within regional spatial planning system. Case study of Moscow oblast՚ - Krasilnikova, Elina; Goncharik, Alesya (TeMA - Journal of Land Use, Mobility and Environment, 2022)
<span class="NormalTextRun SCXW216680332 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"00000000-0000-0000-0000-000000000000|0","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Tahoma",469777842,"Tahoma",469777844,"Tahoma",469769226,"Tahoma",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]">This article is devoted to the landscape and urban planning system formation issues of the Moscow region, based on the integration of landscape and urban planning approaches. The current proposal considers the landscape both as a system and as an active part of the completely urban planning process. The article aims to present landscape and urban planning as systemic tools for transforming the spatial and planning structure of the macro-region - the Moscow region, offering opportunities for the physical and spatial restructuring of regional landscapes into a single green infrastructure of the region. The relevance of the study is related to the lack of documents in the Town Planning Code of Russia substantiating the need for the development of landscape planning projects, which are necessary for the landscape and urban planning system formation of cities, agglomerations, provinces, regions. In creating the landscape and urban planning system of the Moscow region, it is necessary to rely on the theory and practice of landscape urbanism, which shows the possibilities of its active use in the modern process of urban planning development. Furthermore, this article specifies modern research in the landscape and urban planning transformation field of spatial planning structures at the macro-regional level (macro-regional scale). The article will be useful for training researchers and specialists who could improve planning methodology and, consequently, existing landscape and urban planning practices.